Aerobic Fitness Is Related to Myocardial Fibrosis Post–Anthracycline Therapy. Issue 2 (February 2021) - Kirkham, Amy Ashley; Paterson, D. Ian; Haykowsky, Mark J.; Beaudry, Rhys I.; Mackey, John R.; Pituskin, Edith; Grenier, Justin G.; Thompson, Richard B.
ABSTRACT: Adjuvant anthracycline chemotherapy for breast cancer is associated with cardiotoxicity and reduced cardiorespiratory fitness (V˙O2peak ). Purpose: We evaluated the impact of anthracyclines on left ventricular function and myocardial tissue characteristics using cardiovascular magnetic resonance (CMR) imaging to determine their relationship with V˙O2peak . Methods: Women with breast cancer who had not yet received treatment (No-AT, n = 16) and had received anthracycline treatment ~1 yr earlier (Post-AT, n = 16) and controls without cancer (CON, n = 16) performed a maximal exercise test and a comprehensive 3T CMR examination, including native myocardial T 1 mapping, where elevated T 1 times are indicative of myocardial fibrosis. ANOVA and linear regression were used to compare CMR variables between groups and to determine associations with V˙O2peak . Subgroup analysis was performed by categorizing participants as "fit" or "unfit" based on whether their V˙O2peak value was greater or less than 100% of reference value for age, respectively. Results: Left ventricular end-diastolic volume, ejection fraction, and mass were similar between groups. Post-AT, T 1 times were elevated (1534 ± 32 vs 1503 ± 28 ms, P < 0.01), and V˙O2peak was reduced (23.1 ± 7.5 vs 29.5 ± 7.7 mL·kg −1 ⋅min −1, P = 0.02) compared with CON. In No-AT, T 1 times and V˙O2peak were similar to CON. In the Post-AT group, T 1 time was associated with V˙O2peak ( R 2 = 64%), whereas in the absence of anthracyclines (i.e., No-AT and CON groups), T 1 time was not associated with V˙O2peak . Regardless of group, all fit women had similar T 1 times, whereas unfit women Post-AT had higher T 1 than unfit CON (1546 ± 22 vs 1500 ± 33 ms, P < 0.01). Conclusions: After anthracycline chemotherapy, an elevated T 1 time suggesting greater extent of myocardial fibrosis, was associated with lower V˙O2peak . However, those who were fit did not have evidence of myocardial fibrosis after anthracycline treatment. Abstract : Supplemental digital content is available in the text.